Sociogenèse de départements en langue française à Istanbul, Bucarest et Sofia au tournant des années 1990 - Christel Troncy (Recherches en didactique des langues et des cultures)
How do projects emerge which, from a sociolinguistic and functional perspective on teaching, resemble transfers of formative models? This paper proposes that the emergence of education in French in the social sciences in the early 90s had different historical paths in Turkey, Bulgaria and Romania within the context of the formation of the European Union (at that time the EEC, then the EC).Our analysis addresses these projects case by case by giving attention to different interpretations of ideological mechanisms. It particularly takes interest in the cooperation that has been established beyond borders and the elements that form « the common project of French education » among these countries. Beyond the unique creation of each program, the similarities that appear lead us to examine the possible emergence of an idiosyncratic training model in the 1990s.